ESTABLISHMENT OF THE REGIONAL POLICY IN UKRAINE - Yavorska, Viktoria; Kolomiyets, Kateryna; Sych, Vitaliy (Human Geography Journal, 2016)
This article deals with establishment of the regional policy in Ukraine. In the context of regionalization of the country the problem of administrative-territorial reform considered as an important element of national strategy on economy development. Development and implementation of state regional policy provides substantial enhancement of the role and responsibility of local state administrations, local authorities, local communities in the development of the regions. Transformation of the regions into the active agents of market economy and further realization them in the international economy within the European community in the future, brings new demands and challenges to strengthen the economic potential of the regions as well as  to ensure their competitiveness for goods and investments in domestic and international markets .